Innovation and visualization : trajectories, strategies, and myths - Ione, Amy (Consciousness, literature & the arts, 2005)
Amy Ione's Innovation and Visualization is the first in detail account that relates the development of visual images to innovations in art, communication, scientific research, and technological advance. Integrated case studies allow Ione to put aside C.P. Snow's "two culture" framework in favor of cross-disciplinary examples that refute the science/humanities dichotomy. The themes, which range from cognitive science to illuminated manuscripts and media studies, will appeal to specialists (artists, art historians, cognitive scientists, etc.) interested in comparing our image saturated culture w